Independent Learning Curriculum: Readiness of Teachers and Madrasah in Bone Regency - Azis, Muhammad Bachtiar; Fitriani, Fitriani; Amin, Arifah; Nurul Kamila, Adinda (DIDAKTIKA, 2024)
This study aims to determine the madrasah readiness in implementing the Independent Learning Curriculum (Kurikulum Merdeka Belajar). The research applies a mixed-method approach, specifically a combination of qualitative and quantitative research with the concurrent triangulation strategy model. Data collection techniques involve interviews, questionnaires, and documentation. The research findings are as follows: 1) Teachers' readiness in implementing the Independent Learning Curriculum, encompassing dimensions such as a) teachers' knowledge falls into the "ready" category; b) self-development efforts are categorized as "ready"; and c) teachers' readiness in teaching is also categorized as "ready." Therefore, we can conclude that, overall, teachers fall into the "ready" category. 2) The readiness of facilities and infrastructure at MTsN 1 Bone in implementing the Independent Learning Curriculum, which includes the following dimensions: a) Capacity and capacity in â€œreadyâ€ category; b) Learning facilities and infrastructure in â€œreadyâ€ category; c) Supporting facilities and infrastructure in â€œreadyâ€ category. The results of research on the Independent Learning Curriculum have made an important contribution in understanding the effectiveness, factors that influence success, and effective implementation models of the Independent Learning Curriculum. The contribution of this research is also useful for the government, schools, and teachers in implementing the Independent Curriculum effectively and achieving the expected educational goals, especially at the Madrasah level.